Variabilidade de elementos meteorológicos e de conforto térmico em diferentes ambientes na Amazônia Brasileira - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2015)
The study of urban climate in the Amazon is extremely important because the high rates of deforestation related to urbanization generate complex environmental changes and greater disturbances between the soil-plant-atmosphere system. The goal of this study is to analyze the average hourly and monthly variability of air temperature, relative and specific humidity, solar radiation and precipitation in different environments in the Brazilian Amazon to emphasize the effect of urbanization and geographic location the same. This study was conducted in cities of the Belém (PA) and the Manaus (AM) and FLONA Caxiuanã (PA). The data were obtained from automatic weather stations using Campbell Scientific dataloggers (CR100 model), located above the canopy in FLONA Caxiuanã and 1.5 meters from the surface in the cities, both of which had typical urban characteristics. Measurements were taken at 30 minute intervals between 2009 and 2013. Statistical analysis was performed using the nonparametric Kruskal-Wallis test, with a 0.05 significance level. The results indicated that precipitation was the meteorological element with greater variation, both between locations and seasonally. For air temperature, relative moisture and solar radiation, the monthly variation was small, and was instead mostly characterized by seasonal and hourly variations. The heat index also showed little difference between the sites studied, however at the FLONA Caxiuanã the values were lower, highlighting the importance of green areas for improving the thermal comfort of the Amazon region. This is emphasized further in the air temperature data at the FLONA Caxiuanã, which was significantly lower than those observed in the cities. This attenuation of temperatures and thermal comfort in intensely vegetated and preserved areas emphasizes the need for preservation of Amazonian green areas to improve the quality of life for the inhabitants of Amazonia.
Keywords: Clima urbano; Variabilidade; Amazônia; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS DE ECOSSISTEMAS AMAZÔNICOS